The Implementation of Advocacy Method on Learning English Speaking at Senior High School - Anida, Ai Siti; Rohadi, Tedi; Rifai, Ahmad (English Education: Jurnal Tadris Bahasa Inggris, 2024)
In a classroom learning environment, appropriate learning methods are essential for success. Effective methods help teachers deliver material optimally and enable students to absorb it effectively. The advocacy learning method, which is student-centered and debate-based, fosters critical thinking, increases confidence in speaking English, and deepens students' insights. This study aims to: 1) describe the implementation of advocacy methods in classroom learning, and 2) gather students' opinions on the advocacy method used during lessons. A descriptive qualitative research design with a case study approach was employed. Data were collected through observation, interviews, and documentation. Findings indicate that: 1) the advocacy method is effectively implemented in senior high school English classes, fulfilling all necessary elements of debating activities and encouraging students to speak English more confidently, and 2) students' responses to the advocacy method are generally positive, as evidenced by their enthusiasm and data from interviews, observations, and documentation